O10.2 A performance evaluation of the atlas genetics ltd io® system: a novel and rapid point-of-care in vitro diagnostic test for chlamydia trachomatis. (8th July 2017) - Cousins, Emma; Harding-Esch, Emma; Chow, Christine S-L; Phillips, Laura T; Hall, Cathrine; Cooper, Nick; Fuller, Sebastian S; Pearce, David; Green, Marc; Bannister, Stephanie; Clarkson, John; Dunbar, Kevin; et al.
Abstract : Introduction: Rapid Point-Of-Care Tests (POCTs) for Chlamydia trachomatis (CT) may reduce onward transmission and reproductive sexual health (RSH) sequelae by reducing turnaround times between diagnosis and treatment. The io single module system (Atlas Genetics Ltd) runs clinical samples through a microfluidic CT cartridge, delivering results in 30 min. We evaluated its performance in four RSH clinics. Methods: 757 females aged >16 provided additional-to-routine self-collected vulvovaginal swab (VVS). Samples were tested fresh on io within 7 days of collection or were frozen at −80°C for later testing. The io CT-assay performance was compared against clinic BD ViperTM Nucleic Acid Amplification Test (NAAT), with discrepant results resolved on the Artus CT/NG assay. The gold standard for discrepants required agreement from 2/3 tests. Factors associated with CT infection were analysed using logistic regression. Results: Insufficient volume (n=3), missing clinic NAAT data (n=21), and 'invalid' (n=24), where io failed to give a result on two successive runs, meant final analyses were conducted on 709 women (94.3%). CT prevalence was 7.2% (51/709). Sensitivity, specificity, positive (PPV) and negative (NPV) predictive values were respectively: 96.1% (95% Confidence Interval (CI): 86.5–99.5), 97.7% (95% CI: 96.3–98.7), 76.6% (95% CI: 64.3–86.2) and 99.7% (95% CI: 98.9–100). There was no significant difference in performance between fresh and frozen samples, or between symptomatic and asymptomatic patients. Risk factors associated with CT infection were sexual contact CT only. Conclusion: The io CT-assay is the only 30 min, fully automated, high-performing NAAT currently CE-marked for CT diagnosis in women, making it a highly promising diagnostic, to enable specific treatment, initiation of partner notification and appropriately intensive health promotion at the point of care.